Influencia del acoso escolar en las relaciones interpersonales de los estudiantes del Colegio Bachillerato Pindal en el periodo noviembre 2016-diciembre 2017 y la intervención del Trabajador Social - PUCHA JUMBO, GREYS MARIBEL (2018)
This investigative work called influence of the harassment school in LAS relations interpersonal of students of the College BACCALAUREATE PINDAL in the period November 2016 - December 2017 and the intervention of the SOCIAL worker responds to one of the problematic that it afflicts society, bullying occurs in public and private institutions, so the aim of the inquiry is to contribute to the improvement of interpersonal relations in the ninth year of education General basic parallel "A" and "B" of the College baccalaureate Pindal, through a proposal of social action aimed at the prevention of bullying. In relation to methodology used the scientific method, supported the inductivo-deductivo, analitico-sintetico, same observation and survey, that allowed to know and detail the problem of bullying, its causes and consequences, where the hardest they are students because it not allowed to have a harmonious coexistence between companions / os, generating mistrust and conflicts in the classroom. Sample of the research was of 73 students, 73 mothers and parents and 10 teachers of the ninth parallel years A and B, which revealed that harassment affects the relationships of the school already that the abuse by the agr esores make in the classroom there are conflicts, where the strong dominate and the weak are subjected to assaults, which entails that students / you have fear and fear, problems to relate to others, depression and nervousness, low qualifications, school failure, disobedience to teachers, mothers and parents and few desire to attend the school, same that affect interpersonal and social development of the learner. The profession of social work in education constitutes a significant contribution in the resolution and prevention of bullying, so was prepared conclusions and recommendations taking into account the opinion of those involved in the research.